Mechanistic insights into anticancer properties of oligomeric proanthocyanidins from grape seeds in colorectal cancer. (19th April 2018) - Ravindranathan, Preethi; Pasham, Divya; Balaji, Uthra; Cardenas, Jacob; Gu, Jinghua; Toden, Shusuke; Goel, Ajay
Abstract: Although the anticancer properties of oligomeric proanthocyanidins (OPCs) from grape seeds have been well recognized, the molecular mechanisms by which they exert anticancer effects are poorly understood. In this study, through comprehensive RNA-sequencing-based gene expression profiling in multiple colorectal cancer cell lines, we for the first time illuminate the genome-wide effects of OPCs from grape seeds in colorectal cancer. Our data revealed that OPCs affect several key cancer-associated genes. In particular, genes involved in cell cycle and DNA replication were most significantly and consistently altered by OPCs across multiple cell lines. Intriguingly, our in vivo experiments showed that OPCs were significantly more potent at decreasing xenograft tumor growth compared with the unfractionated grape seed extract (GSE) that includes the larger polymers of proanthocyanidins. These findings were further confirmed in colorectal cancer patient-derived organoids, wherein OPCs more potently inhibited the formation of organoids compared with GSE. Furthermore, we validated alteration of cell cycle and DNA replication-associated genes in cancer cell lines, mice xenografts as well as patient-derived organoids. Overall, this study provides an unbiased and comprehensive look at the mechanisms by which OPCs exert anticancer properties in colorectal cancer. Abstract : A comprehensive analysis of gene expression and pathway alterations that are mediated by OPCs present in GSE was identified by genome-wide RNA sequencing in colorectal cancer cells and validated animal models and patient-derived organoid models.